2019
DOI: 10.3390/met9030303
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evaluation and Corrosion Resistance of Semisolid Cast A356 Alloy Processed by Equal Channel Angular Pressing

Abstract: As-cast and semisolid casting using a cooling slope A356 alloy were processed by equal channel angular pressing (ECAP) for Si and grain refinement. The ECAP was conducted at room temperature in a mold, with a channel angle of 120°, and this resulted in a significant size reduction of grain and Si particles from 170.5 and 4.22 to 23.12 and 0.71 µm, respectively, after six passes of heat-treated cooling slope casting, using the ECAP process. The hardness increased with ECAP processing, from 61 HV, for the as-cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…During the formation of DHES, the RS machining chips undergo a series of deformations (mechanical cutting, compaction, extrusion at elevated temperature with dimensional changes), during which the eutectic Si and intermetallic phases are significantly refined and uniformly redistributed into the fine-grained α-Al matrix so that the resulting DHES microstructure is homogeneous and refined (Figure 3). In this way, a larger number of galvanic microcells are formed between ultrafine Si particles (or IMCs) and α-Al grains, resulting in a favourable small cathode/large anode combination and reducing the susceptibility to pitting corrosion [28]. It should not be forgotten that this process generates a larger number of grain boundaries, a greater proportion of unbalanced grain boundaries, dislocations, and residual stresses in the machined sample.…”
Section: Surface Analysis After Corrosion Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the formation of DHES, the RS machining chips undergo a series of deformations (mechanical cutting, compaction, extrusion at elevated temperature with dimensional changes), during which the eutectic Si and intermetallic phases are significantly refined and uniformly redistributed into the fine-grained α-Al matrix so that the resulting DHES microstructure is homogeneous and refined (Figure 3). In this way, a larger number of galvanic microcells are formed between ultrafine Si particles (or IMCs) and α-Al grains, resulting in a favourable small cathode/large anode combination and reducing the susceptibility to pitting corrosion [28]. It should not be forgotten that this process generates a larger number of grain boundaries, a greater proportion of unbalanced grain boundaries, dislocations, and residual stresses in the machined sample.…”
Section: Surface Analysis After Corrosion Measurementsmentioning
confidence: 99%
“…Solid recycled specimens exhibited an excellent combination of high strength and high elongation to failure at room temperature, which was attributed to the refined microstructure, but lower corrosion properties, attributed to the excessive iron contamination that promoted galvanic corrosion [25]. Several researchers have investigated the influence of ECAP on the corrosion properties of aluminium alloys [26][27][28][29][30][31]. They found that the ECAP processing facilitated passivation, increased the thickness of the oxide layer, and the decreased corrosion rate, which was attributed to the significantly reduced grain size in solid recycled specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was reported that the forced convection induced by TMF break the dendrites, refine the grain size, and promote liquid feeding, leading to a decrease in the volume fraction of the porosity and improved mechanical property. The microstructural evaluation and corrosion resistance of a semisolid Cast A356 alloy were studied by Gebril et al [2]. For that, a combination of as-cast and semisolid casting using a cooling slope processed by equal channel angular pressing (ECAP) was used.…”
Section: Casting Aluminum Alloymentioning
confidence: 99%
“…Furthermore, these techniques are expected to serve as alternatives to traditional casting processes because they offer the possibility of constructing defect-free, heat treatable and near-net shape components at low cost [ 8 , 9 ]. This approach produces materials that possess homogeneous globular microstructures that are characterised by decreased segregation and porosity [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%